Genetic and chemical interrogation of the transcription factor PfMyb1 during plasmodium falciparum proliferation and differentiation - Birkholtz, Lyn-Marie (University of Pretoria, 2024)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2023.